Journeyman wizard a magical mystery - Zambreno, Mary Frances, 1954- (New York : Hyperion, 1996)
When Jermyn goes to Land's End to study wizardry under the famous spellmaker Lady Jean Allons, he finds his lessons disrupted by magical mayhem and a mysterious murder.
Sequel to: A plague of sorcerers.
All Ages.
Keywords: Wizards -- Fiction; Magic -- Fiction; Mystery and detective stories